THE PORTRAIT OF LGBT PRACTICES IN CHILDREN ANIMATION - Gultom, Eva Solina; Nuru, Sarniati (Seshiski: Southeast Journal of Language and Literary Studies, 2024)
Media and power are inseparable. In this context, Netflix uses its authority including intellectual agents behind the scenes who have an interest in spreading the doctrine of LGBT ideology and gender inclusion so that it can be accepted by the public including children who are considered vulnerable. This study inquires how LGBT ideology is reproduced in the form of children's animation themes. This study focuses on the pattern of interaction and the spread of LGBT ideology packaged in the form of a children's movie commodity entitled Nimona. The method used in this study is a descriptive qualitative approach involving library research. This study shows that the existence of LGBT practices depicted through two prominent characters is no longer shown as a taboo and immoral commodity but is considered as something normal and worthy of consumption and respect.